(3QaY GdMLH GdeSJhQI Yf eMGSf GdebUhQIs - (3CHi GdbGSe eMeO Hf CMeO Hf eMeO GdMSjfjs; (3MGRe GdbQWGLfj , MGRe Hf eMeO Hf MSf Hf MGRe, CHh GdMSf,J (B684 (3g` s
(3ChdgG (B:s
(3eHJhQI , hGhd GdehLhO ajgG(B: (3hGdXYjfI GdeQCI eGOGeJ ai GdghOL , aEPG de Jcf ajg djSJ HXYjfI hjbGd CXYf HVe GdYjf hgh GdCUd hXYf HSchfgG hgh jTHg bhd HTGQ s
(3BNQgG (B:s
(3hGJjJ HeG jMUd efg GdbGQF Ydi QTGO abO hajJ HeG hYOJ s
(3fSNI SGOSI JJab ai ChdgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3HBNQ UaMGJgG JYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs